Microbiological quality of some selected fresh fruit juices served in Dessie town’s charming cafes and restaurants, nestled in the heart of north-eastern Ethiopia - Moges Kibret Wondimagegn; Siraj Assen Mohammed (Discover Food)
Abstract Fruit juices are vital in human diets, but poorly prepared ones can cause foodborne illnesses. Therefore, this study aimed to assess the safety and microbiological quality of mango, avocado, and papaya juices served in cafes and restaurants in Dessie town. Fifty-four fruit juice samples were aseptically collected from six selected sites and transported to the laboratory using ice boxes. Microbiological quality was assessed according to standard protocols in microbiology. The antibiogram tests were conducted for isolated bacteria following the Kirby-Bauer, disk diffusion method. Additionally, structured questionnaires were distributed to 20 fruit juice makers to collect preliminary information on their hygiene and safety practices in making and handling fruit juices. The findings of this study revealed varying microbial loads (in log CFU/mL) across different fruits; mango exhibited the highest total aerobic viable bacterial count (6.94 ± 0.89), E. coli (6.80 ± 0.11) was dominant in papaya, coliform bacteria were abundant in papaya (6.99 ± 0.89), S. aureus was notably present in avocado (6.88 ± 0.11), Salmonella was maximum in mango (5.77 ± 0.89), while yeast (6.68 ± 0.11) and mold (6.57 ± 0.11) were prominent in mango samples. The bacterial isolates tested for antibiotic susceptibility against thirteen commonly used antibiotics, revealed that all isolated bacteria, except S. aureus were resistant to oxacillin. Conversely, all isolates were sensitivity to chloramphenicol, ciprofloxacin, and norfloxacin. Generally, the microbiological quality of the majority of fruit juices served to consumers was found to be unsafe compared to the Gulf standard. Therefore, enforcing ongoing training for juice producers and regular health officer’s inspection is vital to maintain proper hygienic practices.